Pengaruh Dewan Komisaris Independen, Kepemilikan Manajerial, Kualitas Audit, Komite Audit, Dan Leverage Terhadap Integritas Laporan Keuangan - Kartika Sandra; Kusumawati, Eny (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Financial report integrity is a condition where information in financial reporting is disclosed fairly, transparently and honestly, without any manipulation or distortion that could mislead report users. This research analyzes the influence of an independen board of commissioners, managerial ownership, audit quality, audit committee, and leverage on the integrity of financial reports in companies in the basic materials sector on the Indonesia Stock Exchange for the 2021-2023 period. The sampling technique used in this research was purposive sampling. A total of 117 companies have met the criteria as observation units. The analytical method used is multiple linear regression analysis and has passed the classical assumption test. The research results provide empirical evidence that the independen board of commissioners variable and audit quality have a significant influence on the integrity of financial reports. Meanwhile, managerial ownership, audit committee and leverage have no effect on the integrity of financial reports. With the integrity of financial reports, stakeholders such as investors, creditors and regulators can make economic decisions with more confidence and based on correct information.